Come! I’ll See You In The Library - Ece Dündar (Türk Kütüphaneciliği)
The article describes the initiative “Come! I'll See You in the Library”, projected by Milan Municipality Public Library System. The initiative, involvingfive neighborhood libraries, located in peripheral areas, is centered on animation activities (lectures, cooking courses, information literacy lessons, etc.) organized together with cultural associations. The aim is to strengthen the role of public libraries of Milan in supporting social cohesion, especially towards immigrants.